Tracing The Roots Of Agriculture: The Foundation Of Early Human Survival - Balkrishna, Acharya; Mittal, Rashmi (PURBAWIDYA, 2025)
A pivotal issue in world prehistory is determining whether population migration or cultural diffusion played a more crucial role in the dissemination of agriculture across various regions. An often neglected yet significant aspect of this debate is the examination of preserved crops and weeds from early agricultural societies. Research utilizing archaeobotanical data from diverse sites has revealed distinctive vegetation patterns linked to specific regions occupied by early populations. The findings suggest that a broad range of plant species at early agricultural sites were likely utilized for food, and there is no evidence of a reduction in plant food diversity as agriculture expanded. These observations provide valuable insights into the process of crop domestication, indicating a symbiotic relationship between humans and plants may have been instrumental in the advancement of agriculture. This review article underscores the presence of early agricultural sites across distinct domestication centre across Asia including Ohalo II, Jiahu, and Xinglonggou showing that early plant cultivation developed in varied ecological settings, often predating or extending beyond the conventional Neolithic timeline. The evidences provided are derived from existing excavation reports, and there remains the possibility that upcoming findings could extend these dates even more.